PEMETAAN KEBUTUHAN GAYA BELAJAR DAN MINAT BELAJAR ERA TRANSFORMASI DIGITAL PENDIDIKAN PADA SISWA KELAS VIII MATA PELAJARAN SKI DI MTsN - Imamah, Rizkia Fifiqotul; Hidayah, Nurul lailatul (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT The development of education in the digital era requires educators to gain a deep understanding of students’ learning characteristics in order to create effective and meaningful learning processes. In the context of Islamic Cultural History (SKI) learning at MTsN 1 Tuban, this study focuses on mapping the learning styles and learning interests of eighth-grade students, as well as examining the use of digital learning media in the instructional process. The study was designed using a qualitative descriptive approach, with data collected through in-depth interviews, participatory observation, and analysis of instructional documentation. The results indicate that students exhibit diverse learning styles, including visual, auditory, and kinesthetic, with visual learning being the most prominent. The use of digital learning media such as visual presentations, instructional videos, and interactive quizzes was shown to enhance students’ learning interest and engagement in SKI learning. Nevertheless, the implementation of digital learning continues to face several challenges, including limited availability of devices, internet connectivity constraints, and teachers’ readiness to systematically map students’ learning styles. This study concludes that digital-based mapping of learning styles and learning interests plays an important role as a foundation for designing differentiated and student-centered SKI learning in the era of digital transformation. ABSTRAK Perkembangan pendidikan di era digital menuntut pendidik untuk memahami secara mendalam karakteristik belajar peserta didik guna mewujudkan proses pembelajaran yang efektif dan bermakna. Dalam konteks pembelajaran SKI di MTsN 1 Tuban, penelitian ini difokuskan pada pemetaan gaya belajar dan minat belajar siswa kelas VIII serta kajian terhadap pemanfaatan media pembelajaran digital dalam proses pembelajaran. Penelitian ini dirancang menggunakan pendekatan kualitatif deskriptif dengan tahapan pengumpulan data meliputi wawancara mendalam, observasi partisipatif, dan analisis dokumentasi pembelajaran. Hasil penelitian menunjukkan bahwa keberagaman gaya belajar siswa mencakup visual, auditorial, dan kinestetik, dengan gaya belajar visual sebagai kecenderungan yang paling menonjol. Penggunaan media pembelajaran digital, seperti presentasi visual, video pembelajaran, dan kuis interaktif, terbukti mampu meningkatkan minat serta keterlibatan siswa dalam pembelajaran SKI. Meskipun demikian, pelaksanaan pembelajaran digital masih menghadapi sejumlah kendala, antara lain keterbatasan perangkat, akses jaringan internet, serta kesiapan guru dalam melakukan pemetaan gaya belajar secara sistematis. Penelitian ini menyimpulkan bahwa pemetaan gaya belajar dan minat belajar berbasis digital berperan penting sebagai dasar perancangan pembelajaran SKI yang berdiferensiasi serta berorientasi pada peserta didik di era transformasi digital.